Pengaruh Penggunaan Media Kahoot terhadap Minat Belajar Siswa pada Mata Pelajaran IPAS Kelas IV di SDN 1 Pringga Jurang - Muhamad Hazrul Hidayat; Heri Hadi Saputra; Setiani Novitasari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Students' interest in learning science subjects has an important role in supporting learning success, but conditions in class IV of SDN 1 Pringga Jurang show that students' interest in learning is still low, which can be seen from the lack of attention, involvement, and enthusiasm of students during the learning process which is still dominated by conventional methods. This study aims to determine the effect of the use of Kahoot media on students' interest in learning science subjects in grade IV of SDN 1 Pringga Jurang. This study uses a quantitative approach with a Quasi Experimental Design research type in the form of One Group Pretest-Posttest Design. The subjects of the study were all 24 students of grade IV of SDN 1 Pringga Jurang. Data collection techniques in this study include questionnaires and observations. Data analysis was carried out through prerequisite tests including normality tests and homogeneity tests, then continued with hypothesis testing using Paired Sample T-test and Effect Size calculations. The results of the normality test showed that the pre-test data had a significance value of 0.645 and the post-test data of 0.357 (Sig. > 0.05), indicating that the data were normally distributed. Meanwhile, the homogeneity test showed a significance value of 0.086 (Sig. > 0.05), indicating that the data were homogeneous. The results of hypothesis testing obtained a Sig. (2-tailed) value of 0.001 <0.05 and a calculated T value > T table of 21.285 > 2.064, so it can be concluded that there is an effect of the use of Kahoot media on students' interest in learning science subjects in grade IV of SDN 1 Pringga Jurang. The effect size test results obtained a d-value of 4.345, which falls into the strong effect category. Therefore, it can be concluded that the use of Kahoot media has a strong influence on students' learning interest, as indicated by indicators of enjoyment, interest, attention, and engagement in learning.